Seminar dan Pelatihan Penulisan Karya Tulis Ilmiah bagi Siswa MTs Raudlatul Munawwaroh Jatirejo Pringsewu - Nurmitasari, Nurmitasari; Astuti, Robia; Khasanah, Binti Anisaul; Hidayatulloh, Hidayatulloh (Bagimu Negeri, 2019)
The implementation of Community Service activities was carried out through a seminar and training on writing scientific papers for students of MTs Rhaudlotul Munawwaroh Jatirejo Pringsewu. The results of this activity include: (1) can grow students' interest in writing, (2) students are able to write reports on tourism activities in accordance with EYD and scientific writing writing guidelines (3) students become trained to think scientifically, and (4) students able to be competitive in participating in the Youth Scientific Work competition in the local / national / international arena. Keywords: writing, scientific thinking, scientific writing